Investigating English Language as a Tool of Cultural Manipulation in English Medium Schools and Universities in Khulna City, Bangladesh - Md. Obaidullah (Pusat Studi Bahasa dan Publikasi Ilmiah, 2022)
This study follows a quantitative research design to investigate the perception of students from English medium schools and universities towards English language learning and cultural manipulation in Bangladesh. A total of 300 students from three English medium schools, two private universities and two public universities participate in the survey. A simple random sampling technique is followed to define the sample size. Further, the study uses a questionnaire as a tool for collecting data. Then, Statistical Package for the Social Sciences (SPSS) 21.0 software is used for analyzing the data. The findings reveal that majority of the respondents are practicing western culture, and therefore, our Bangladeshi culture is gradually being replaced. Though English language has been playing a great role for the communication, it has become a threat to our own culture. The students are much more attracted to western culture and lifestyle neglecting Bangladeshi ones. They start adopting western culture to the detriment of Bangladeshi tradition and culture. Finally, the paper concludes confirming that such kind of excessive indulgence in western culture undermines Bangladeshi traditional values and ways of life. The government along with the language policy makers should emphasize how the native culture and the target culture can be represented in a more sensible and balanced way.